Multicolour photometry and Gaia EDR3 astrometry of two couples of binary clusters (NGC 5617 and Trumpler 22) and (NGC 3293 and NGC 3324). Issue 4 (10th March 2021) - Bisht, D; Zhu, Qingfeng; Yadav, R K S; Ganesh, Shashikiran; Rangwal, Geeta; Durgapal, Alok; Sariya, Devesh P; Jiang, Ing-Guey
ABSTRACT: This paper presents a comprehensive analysis of two pairs of binary clusters (NGC 5617 and Trumpler 22) and (NGC 3293 and NGC 3324) located in the fourth quadrant of our Galaxy. For this purpose, we use different data taken from VVV survey, WISE, VPHAS, APASS, and GLIMPSE along with Gaia EDR3 astrometric data. We identified 584, 429, 692, and 273 most probable cluster members with membership probability higher than 80 per cent towards the region of the clusters NGC 5617, Trumpler 22, NGC 3293, and NGC 3324. We estimated the value of R=A_VE(B-V) as ∼3.1 for the clusters NGC 5617 and Trumpler 22, which indicates the normal extinction law. The values of R 3.8 and ∼1.9 represent the abnormal extinction law towards the clusters NGC 3293 and NGC 3324. Our kinematical analysis shows that all these clusters have circular orbits. Ages are found to be 90 ± 10 and 12 ± 3 Myr for the cluster pairs (NGC 5617 and Trumpler 22) and (NGC 3293 and NGC 3324), respectively. The distances of 2.43 ± 0.08, 2.64 ± 0.07, 2.59 ± 0.1, and 2.80 ± 0.2 kpc estimated using parallax are consistent with the values calculated by using the distance modulus. We have also identified 18 and 44 young stellar object candidates present in NGC 5617 and Trumpler 22, respectively. Mass function slopes are found to be in fair agreement with the Salpeter's value. The dynamical study of these objects shows a lack of faint stars in their inner regions, which leads to the mass-segregation effect. Our study indicates that NGC 5617 and Trumpler 22 are dynamically relaxed but the other pair of clusters are not. Orbital along with the physical parameters show that the clusters in both pairs are physically connected.